2021
DOI: 10.1063/5.0074842
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-classical hybrid algorithm for the simulation of all-electron correlation

Abstract: While chemical systems containing hundreds to thousands of electrons remain beyond the reach of quantum devices, hybrid quantum-classical algorithms present a promising pathway toward a quantum advantage. Hybrid algorithms treat the exponentially scaling part of the calculation—the static correlation—on the quantum computer and the non-exponentially scaling part—the dynamic correlation—on the classical computer. While a variety of algorithms have been proposed, the dependence of many methods on the total wave … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 81 publications
0
21
0
Order By: Relevance
“…We now turn our attention to the wave function component of MC-PDFT. Although, in principle, PDFT may be combined with any wave function method or even density matrix methods, 27,28 the most explored direction so far for surpassing the capabilities of KS theory comes from combining PDFT with explicitly multicongurational wave functions, mainly MCSCF. The most popular version of MCSCF is complete active space SCF, 29 abbreviated CASSCF.…”
Section: Mc-pdft and Mc-neftmentioning
confidence: 99%
“…We now turn our attention to the wave function component of MC-PDFT. Although, in principle, PDFT may be combined with any wave function method or even density matrix methods, 27,28 the most explored direction so far for surpassing the capabilities of KS theory comes from combining PDFT with explicitly multicongurational wave functions, mainly MCSCF. The most popular version of MCSCF is complete active space SCF, 29 abbreviated CASSCF.…”
Section: Mc-pdft and Mc-neftmentioning
confidence: 99%
“…Furthermore, while molecular simulations generally require handling the N‐electron wavefunction, recently proposed approaches have instead focused on the expression of the ground‐state energy as a function of the two‐electron reduced density matrix 361,362 . While recent results have indicated that they represent a promising direction for efficient molecular quantum simulations, additional research is needed to assess their full potential.…”
Section: Quantum Algorithms For Chemistrymentioning
confidence: 99%
“…Boyn el al. [9] obtained active-space 2-RDMs from quantum computations and post-processed them with two classical correlation methods, the anti-Hermitian contracted Schrödinger equation (ACSE) theory [10][11][12] and multiconfigurational pair-density functional theory (MC-PDFT) [13]. Fujii el al.…”
Section: Introductionmentioning
confidence: 99%